Metacognitive as One of the Strategy in Teaching Reading Comprehension - Luthfiyyah, Roghibatul; Perdani, Laena Kusuma (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2014)
This study aims at investigating further about the effectiveness ofMetacognitive Strategy implementation for students' reading comprehension at the second grade of SMA Negeri 1 cilimus and finding the students' responses vividly after learning reading comprehension through Metacognitive Strategy at the second grade of SMA Negeri 1 cilimus.The method that used in this study was Quasi Experimental Research with pre-test post-test non-equivalent group design. The population of this study was the second grade students of  SMAN 1 Cilimus in the academic year 2014/2015; itconsists of eight classes. Two classes were as samplewhich were taken by purposive sampling, they were XI MIA 3 as experimental class and XI MIA 1 as control class.The use of Metacognitive Strategy was proven as an effective technique for teaching reading comprehension.It showed that there were the significantvalue of the implementation of KWL chart as a metacognitive strategy in teaching reading comprehension. In addition, the implementation of KWL chart had strong responses from the students. It could be seen from the result ofquestionnaire that described the strong responses of students toward the implementation of KWL chart as the metacognitive strategy. It could be concluded that the use of KWL chart as metacognitive strategy was effective in teaching reading comprehension. Thus, teachers probably use this technique as one of the variation for teaching reading comprehension.